BUDAYA ORGANISASI MEMODERASI PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU (Studi Pada Guru SMA PGRI Kabupaten Pati) - Endang Sri Rrahayu, 12.52.02.0187 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze that moderate the organizational culture of school leadership and professional competence of the teachers performance SMA PGRI in Pati regency.This study used a population of 131 teachers who work at SMA PGRI in Pati regency. Measurements using a Likert scale of 5 (five) alternative answers. Mechanical testing of the data used in this study include testing the validity of the factor analysis, reliability testing with Cronbach alpha formula, multiple regression analysis, and the significance test, the coefficient of determination to prove the truth of the research hypothesis.The results showed that; school leadership does not affect the performance of teachers, professional competence and a significant positive impact on teacher performance, cultural organizational positive and significant impact on teacher performance, organizational culture does not moderate the effect of school leadership on teacher performance, organizational culture does not moderate influence on the performance of professional competence teacher at SMA PGRI in Pati regency. Keywords : school leadership, professional competence, organizational culture,Â  teacher performance